Investigating Quantum-Resilient Security Mechanisms for Flying Ad-Hoc Networks (FANETs) - Abbood, Abdulnasser AbdulJabbar; AL-Shammri, Faris K.; Alzamili, Zainab Marid; Al-Shareeda‬‏, ‪Mahmood A.; Almaiah, Mohammed Amin; AlAli, Rommel (Universitas Muhammadiyah Yogyakarta, 2025)
Flying Ad Hoc Networks (FANETs) are indispensable in applications such as Surveillance, Disaster response missions, and Military operations. Both security and communication efficiency must meet certain requirements. However, their effectiveness is hobbled by dynamic topologies, resource constraints, and cyber threats. Therefore, Post-Quantum Cryptography (PQC) is necessary. Classical algorithms and current PQC schemes for FANETs have been discussed in this thesis, including cryptographic solutions that are lightweight enough for resourceconstrained environments. The numerical results of the experiment show that while lattice-based cryptography involves minimal risk of breaches, its power consumption is 25% higher than that for other systems and its processing time 30% slower. In contrast, multivariate polynomial cryptography is better on metrics like usage of electricity: only 10% more power consumed energywise and 15% more CPU cycles needed for processing. The introduction of PQC algorithms and architectures resulted in a 5–10% reduction in network throughput and increased latency to 20% in some scenarios. The results show that hybrid cryptographic systems—combining classical with PQC techniques— have the potential to achieve both high efficiency and long-term security. Case studies have validated the feasibility of tailored quantum-safe algorithms in FANETs, which can offer considerable security benefits while standing rigorous scrutiny in terms of scalability and computational performance on dynamic, missioncritical operations.